PENGARUH INVESTASI PUBLIK TERHADAP PERTUMBUHAN PERUSAHAAN LOGISTIK - Palasa, Philia; Firdaus, Salsabila; Fitrianingsih, Kukuh; Juliyani, Juliyani; Dwicahyo, Fiqri Septiadi (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
In Indonesia, the growth of logistics companies has experienced significant dynamics in line with the increasing volume of domestic and international trade. This research explores the impact of public investment on the growth of logistics companies in Indonesia, with a focus on infrastructure and information technology. The research subjects include managers or leaders of logistics divisions from each logistics company. Data collection is conducted through in-depth interviews, observation, and document analysis. The data obtained is analyzed using thematic analysis techniques. The research findings indicate that public investment in toll road construction and port facility improvements enhances operational efficiency by accelerating goods delivery and reducing travel time. Additionally, information technology support through transportation management systems and GPS tracking reduces operational costs by optimizin g routes and managing fleets more effectively. The findings also show that improvements in infrastructure and technology synergistically enhance the operational capacity of logistics companies, enabling them to handle larger volumes of goods and expand their service coverage. This study provides valuable insights for policymakers and company management on the strategic benefits of public investment in the logistics sector.